Variations in Implementation of Biology Online Teaching and Learning in Covid-19 Pandemic: A Case Study at Senior High Schools in Palembang, South Sumatra - Iis Damayanti; Kodri Madang*; Meilinda meilinda (Universitas Syiah Kuala, 2022)
In Palembang, almost all the school have been implemented virtual learning, but not every school has complete facilities to support it. In fact, the completeness of facilities such as smartphones, laptops, a stable internet network, and skills in using various digital platforms greatly affect the independence and learning achievement of students. This study aims at discovering the profile of virtual Biology teaching and learning implementation in senior high schools throughout Palembang. This descriptive study was conducted from February to March 2021 with a random sampling technique. The number of 343 student samples was determined using the Slovin formula with an error tolerance of 5%. The samples were five schools in Palembang city, South Sumatera District with varying (A, B, and C) school accreditation levels. Data were collected in two ways, (1) a google form with 45 questions and (2) a six-question interview with Biology teachers from each school. The resulted data were analyzed descriptively. The descriptive analysis of the students’ responses was done by summarizing and presenting them in diagrams. The results showed that in A, B and C accredited high schools, students have similarities in the use of smartphones and laptops in online learning. The most used applications in online learning were WhatsApp and Zoom Meeting. The results of the questionnaire showed that students at all accredited high schools were not accompanied by their parents since they were independent enough. They, furthermore, experienced obstacles such as difficulty understanding the material, lack of concentration, boredom, and unstable internet network